Market Access: Unfinished Business - Post Uruguay Round Inventory and Issues (World Trade Organization (WTO), 2001)
The study profiles post-Uruguay Round market access conditions in three areas - industrial tariffs, agriculture and services - the latter two of which are already the subject of ongoing negotiations.
Keywords: 330